Fast low temperature synthesis of layered perovskite heterojunctions for overall water splitting. (6th November 2020) - Hofmann, Anja; Weiss, Morten; Marschall, Roland
Abstract: The Ba5 Ta4 O15 -Ba3 Ta5 O15 -BaTa2 O6 heterojunction was synthesized for the first time at ambient pressure and mild temperatures without further need of calcination. By systematically adjusting the synthesis parameters, the composition of the composite could be tailored. Detailed Rietveld refinement revealed the highest amount of by-phases for the non-calcined sample with around 12% of Ba3 Ta5 O15 and 12% of BaTa2 O6, respectively. Ba5 Ta4 O15 represented the main phase for all samples. The non-calcined heterojunction showed the highest activity in photocatalytic hydrogen production with 2360 µ mol h −1 m −2 corresponding to 1180 µ mol h −1 without any co-catalyst. A Rh-Cr2 O3 co-catalyst was photodeposited on all samples depending on the surface area for overall water splitting. All samples were active in overall water splitting. This novel synthesis strategy paves the way towards a general low-cost and energy-saving synthesis route to achieve highly crystalline and highly active metal oxide semiconductor photocatalysts.